El pequeño Rey maestro repostero - Sáez Castán, Javier 1964- (Ed. Ekaré, 2013)
The Little King is sick of eating compotes. However, do not despair and becomes a scullery team comprised of snails, crabs and tadpoles. Together they set out to invent a recipe: Mojiganga to Petit Roi. The third story of the famous author Javier Saez Castan tells a risky art of cooking from peculiar methods raid
Keywords: Bakers / Juvenile fiction; Insects / Juvenile fiction; Bakers; Insects